PENGARUH BUDAYA KERJA DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. BANK PERMATA BATAM - Theresia Meyda Ruliani Situmorang; Dhenny Asmarazisa (BENING, 2016)
This research aimed to study the influence of Work Culture and Incentives to Employee Performancefor PT. Bank Permata Batam.This research was conducted with the approached survey that consists variable Work Culture and Incentives(X) and Employee Performance(Y). To prove the influence of Work Culture and Incentives to Employee Performance, the authors collected data by distributing questionnaires as many as 60 respondents as samples taken from Employeement of PT. Bank Permata Batam. Data were collected through questionnaires were processed using program applications statistical Product and Service Solutions (SPSS) version 21. The results showed that the application of Work Culture and Incentives jointly contribute to a positive and significant impact on Employee Performance by 34,4% while the remaining 65,6% is influenced by other factors. The regression analysis partially shows that, variable Work Culture and Incentives has positive and significant effect on Employee Performance. KeyWords :Work Culture, Incentives, Employee Performance.